Outcomes of COMBO therapy for severe mitral regurgitation compared with transcatheter edge-to-edge repair - Yokoyama, Hiroaki; Ruf, Tobias Friedrich; Gößler, Theresa Ann Maria; Geyer, Martin; Zirbs, Julia; Schwidtal, Ben Luca; Münzel, Thomas; von Bardeleben, Ralph Stephan (Frontiers in Cardiovascular Medicine, 2024)
Background: There are different types of transcatheter mitral valve repair (TMVr) currently in clinical use, including leaflet approximation, annular cinching, and restoration of the chordal apparatus of the mitral valve (MV). While the concomitant combination (COMBO) therapy of transcatheter edge-to-edge repair (M-TEER) with another TMVr concept has been proven feasible, potentially offering patient-tailored treatment for severe mitral regurgitation (MR), a comparison to M-TEER alone has not been made. Aims: To evaluate the procedural and clinical outcome of COMBO therapies compared with M-TEER alone. Methods: We included consecutive patients undergoing COMBO and M-TEER between March 2015 and April 2018 at our Heart Valve Center, while excluding patients with redo case and previous MV surgery. Procedural outcomes and all-cause mortality were compared between COMBO therapy vs. M-TEER alone. Results: 357 patients (mean age 78.9±7.0 years, 53.2% male, M-TEER n= 322, COMBO n=35; COMBO: MitraClip and the CMCS n=26, MitraClip and Cardioband n=5, and MitraClip and Neochord n=4) were analyzed. Patients with COMBO therapy had larger left chamber sizes, a lower left ventricular systolic ejection fraction (LVEF; COMBO: 37.4±13.8%, M-TEER: 47.9±14.3%, p<0.001), and a more severe MR grade (p<0.001). There were no significant differences in the prevalence of residual MR ≧2+. However, the need for re-intervention, always employing M-TEER, was more common in the COMBO group. During a mean 3.6 year long-term follow-up there was no significant difference of all-cause mortality between both groups (Log rank p=0.921). Conclusions: COMBO therapy may be still a beneficial therapy options for patients with severe MR who already have more dilated LV, more severe MR and more pronounce LV systolic dysfunction. The higher need for re-intervention in the COMBO-group may signal more complex anatomies and possibly underlines the necessity of treating significant MR earlier. Future research is required to establish the COMBO-approach as a toolbox-like treatment option, thus offering a patient-tailored approach depending on the individual anatomy and pathology. Key Words: mitral regurgitation, transcatheter mitral valve repair, TMVr, mitral transcatheter edge-to-edge therapy, M-TEER, COMBO therapy